Ketentuan Pengawas dalam Pelaksanaan BK di Sekolah: Literature Review - Siti Rahmah Tursnia; Neviyarni; Firman (Medan Resource Center, 2022)
The provisions related to supervisors have been regulated in several government regulations. The term supervision in some foreign literature can at least be understood in the context of: (1) inspection, (2) control, and (3) supervision. The three terms above have different meanings. Inspection has the essence of building legal compliance, namely compliance with binding laws and institutional regulations. The duties and responsibilities of supervisors in the field of guidance and counseling refer to (Depdiknas, 2009 which refers to PP No. 74 of 2008). Improving the ability of BK teachers in utilizing the learning environment and improving the ability of BK teachers in preparing and implementing BK programs in schools is one of the objectives of supervision. The elements of supervision are education supervisors, academic and managerial supervision, professional development supervisors, and supporting supervisors. The problem that we often encounter is that there are still many school/madrasah supervisors who do not know and understand the role they must play and the functions they carry out. For this reason, an effort or solution that must be done immediately is that the government should review the performance of school supervisors objectively, then supervisors should be encouraged to take part in supervisory exercises carried out by the government or related agencies in order to know the development of information and improve the competence of a supervisor.